The 'hidden hypothesis'- approach in evaluation methodology: The Swiss participation in the European INTERREG II- Programme - Alain Thierstein; Michel Rey; Manfred Walser; Luc Vodoz (European Regional Science Association (ERSA), 1998)
Regional development, and crossborder cooperation in particular, needs feedbacks on the impacts of public policies. Policy evaluation is one appropriate tool. The ?hidden hypothesis'- approach is characterized by two elements: (1) an emphasis on the invisible goals of an evaluated programme or instrument and (2) a strong orientation towards processes of learning and motivation with the actors involved. (1) The formulation of political programmes tends to integrate as much different interests as possible. Such goal-setting processes simplify political agreement. But to evaluate such programmes with all their different and partly conflicting goals creates problems. The quality of an evaluation cannot be better as the quality of the evaluated goals and conflicting goals lead straight forward to conflicting results. (2) Evaluating the results of a political programme is also confronted with problems of measurement. Evaluation methodology normally distinguishes output, impact and outcome of a programme or a project. In general it is very tricky to evaluate the outcome. Thus the presented approach of evaluation works with different logic. The approach aims at enabling the actors concerned to modify and rearrange their activities. The evaluator acts as moderator and gives inputs for the necessary learning processes. This approach can be used especially in intermediate evaluations and monitoring. The case of the Swiss participation to the European INTERREG II- Programme shows a great complexity concerning political goals and concerning the cooperation in a federalistic political structure. Therefore the casestudy is a good example to demonstrate the advantages of the approach: In 1992 the Swiss population voted against joining the European Economic Market Treaty. The narrow rejection by plebiscite lead to intense discussions about the national cohesion. Afterwards the federal strategy to move the country towards an European integration has been based on a piecemeal approach and small projects of crossborder micro-integration. As an important strategic policy instrument the Swiss government decided to contribute to the INTERREG II- Programme of crossborder cooperation with own ressources of co-financing. In this situation the system of goals connected with the participation in INTERREG II is very complex: The different explicite and implicite goals can be categorized by a double dichotomy: On the one hand the tension between the goal of European integration and the goal of (Swiss) regional development. On the other hand the tension between active policy steering and re-active coordinating. Both relationsships are overlapping and influence the administrative levels between central government and the single local project. To evaluate this policy is a work of great complexity. Key words: evaluation methodology, regional crossborder development, INTERREG, Switzerland
Keywords: 330